Mobilizing dissent: community organizing for informal housing - Zayed, Hatem (AUC Knowledge Fountain, 2014)
Rapid and uneven urban growth across the globe has been accompanied by increasing informality. In Egypt, as the state attempts to address urban housing informality, its urban development plans have been accused of being economically driven, unrepresentative of the demands of residents of informal areas, and threatening to their livelihoods and wellbeing, thus prompting many acts of resistance and dissent by those who dwell in informal areas. This thesis aims to explore reasons behind mobilization of residents of informal areas and their subsequent resistance to state urban plans by addressing a) the role played by the state in framing and identifying the present housing crisis, b) the role played by non-state actors in providing support to the state, and c) the avenues of participation available to residents of informal settlements through which they can partake in the decision-making process. It is hypothesized that resistance occurs within informal settlements in response to the inability of the state to play the role it set out for itself, reflecting a misdiagnosis of the nature of informality and an incomprehensive understanding of the housing crisis. Moreover, while non-state actors have been unable to compensate for the state's shortcomings, and as there are no formal channels of participation available for the residents of informal settlements, communities have found no other way but to resist through informal means. Additionally, this thesis explores the main drivers of social mobilization by examining two case studies, Bab El-Nasr and Ramlet Boulaq. In the latter, residents had been able to successfully mobilize resources and mount strong resistance against state housing policy; while in the former, efforts at resisting state policies were short-lived, scattered, and failed to bring about real change. In these case studies, perception of threat and deprivation, access to moral, cultural, human, material, and socio-organizational resources, along with the presence of networks of trust were found to be determining factors in explaining the transformation of granular acts of protest into structured and patterned collective action.